INTERPERSONAL INTOLERANCE TO SOCIAL UNCERTAINTY AS A FACTOR OF PROFESSIONAL BURNOUT OF TEACHERS (Psychology Travelogs, 2023)
Significant differences in the groups of teachers with different levels of tolerance to social uncertainty in terms of professional burnout were found. The analysis of the data allows us to conclude that the higher the level of interpersonal intolerance to social uncertainty, the higher the levels of emotional exhaustion and depersonalisation of teachers. This is because communicative closeness and alienation inherent in manifestations of interpersonal intolerance to social uncertainty leads to exhaustion of the nervous system and a reduction in the number of communication partners in the professional environment, which hinders professional growth and satisfaction in the performance of professional functions. A high level of interpersonal intolerance to social uncertainty hinders the development of professional success, and, on the contrary, contributes to the lack of involvement of the teacher in the performance of professional duties, low level of responsibility for the results of their own activities. It can be assumed that teachers' rejection of changes contributes to the development of a limited range and intensity of emotional involvement in professional communication, and to the devaluation of their own professional achievements. High emotional involvement of teachers in the lives of students and colleagues, sensitivity to what is happening, allows them to expand the scope of professional interests with the use of non-standard approaches to professional activities. When developing recommendations for the prevention of emotional burnout, it is necessary to take into account these data and promote the manifestation of teachers' own "I" and emotional saturation in professional communication.
Keywords: interpersonal intolerance; social uncertainty; emotional exhaustion; depersonalisation; pedagogical workers